THE POST-TRUTH OF RACIAL FRAMING IN BLACK LIVES MATTER ERA - Febriyanti, Irma (Proceedings of English Linguistics and Literature, 2020)
The year 2020 has a lot on its plate for African Americans to take and conquer. Not only that, they are dying from Covid-19 at higher rates compared to other races due to their pre-existing condition in the U.S., but they also still have to face the battle against racism in this era of Black Lives Matter. Ahmaud Arbery, George Floyd, Christopher Cooper, and Chris Beaty are just a glimpse of violence against Black Americans exposed by social media, showing the world how American society is still corrupted and plagued by white fragility sensibility. Moreover, Black Americans are two-and-a-half times as likely as white Americans to be killed by the police, even though Black Americans only make up 13 percent of the U.S. population. These horrible incidents come from a distinct understanding between White and Black Americans, where Blacks are positioned to have an unshaken presumption of guilt simply because of being Blacks. This study aims at revealing a longstanding disdain for the truth as White people claiming to be fragile and sensible while subverting the reality and perjure themselves to racially framing Black people. In a society that Whites are dominant, Bourdieu’s theory on field, habitus, and capital are used here to analyze the post-truth of racial framing along with White Fragility and White Sensibility in American society coined by Robin DiAngelo.